Xanthophyll pigments dietary supplements administration and retinal health in the context of increasing life expectancy trend - Jurja, Sanda; Negreanu-Pirjol, Ticuta; Vasile, Monica; Hincu, Mihaela Mehedinti; Coviltir, Valeria; Negreanu-Pirjol, Bogdan-Stefan (Frontiers in Nutrition, 2023)
Introduction Medicine faces nowadays the trend of increasing life expectancy of human population, with the resulting increase of degenerative age related diseases prevalence, combined with the risks of less tempered sun radiations environment exposure. Under these circumstances, our work pointed out on evaluating the effect of some xanthophyll pigments dietary supplements, actually widely recommended, for prevention of retinal degenerative damages and for slowing down the progression of such age related changes if they have already occurred. These dietary supplements are already well known for their total antioxidant activity, proven by photochemiluminescence method using Total Antioxidant Capacity in Lipid soluble-substances procedure. Materials and methods The study recruited a number of 120 subjects equally divided on genders. The lot included a first group of 60 patients with comparable ages (all of them over 50 years and divided in 2 segments of age: 50-60 and over 60) and suffering from comparable retinal age-related degenerative abnormalities (mild/medium severity age-related macular degeneration according to Wisconsin Age-Related Maculopathy Grading System), and a second group, considered control, including a similar number of healthy, normal retina subjects belonging to same age and gender categories. There were evaluated at baseline the eye medical status and the retinal risk by specific methods: complete eye check-up, Amsler grid, specific standardized questionnaires focused on visual function and its impact on the quality of current life. Both groups, patients and control, received similar dosages of xanthophyll pigments dietary supplements including lutein and zeaxanthin during 18 months after baseline; at the end of this supplementation period a new evaluation was conducted. In the second part of the research all subjects involved received a new dietary supplement in which the same xanthophylls were enriched with C and E vitamins and oligo-elements Zinc and Copper. At the end of three years duration supplementation, the subjects were reevaluated and the paper presents the conclusions on the matter, pointing on the impact of xanthophyll supplements on visual health. Results Correlation tests were applied to the complete set of data. Correlation tests have values between -1 and +1. The value -1 represents the negative correlation (reverse proportionality) meanwhile the value +1 represents the positive correlation (direct proportionality). The charts show the curves that are fitting experimental data. The dependence is linear in nature, and the value R2, as it approaches more the value 1, represents a better match with the experimental data (the data are in a percentage of approximately 99% on these straight lines of type y = ax + b). In the charts, there were noted the average values of the scores for healthy control patients with “Control”, and the average values of the scores for the patients with existing age related degenerative retinal pathology at baseline with “Patients”. Discussion The retinal function and the impact of visual condition on health were both evaluated at baseline, 18 months and 36 months after baseline, by visual acuity, ophthalmoscopy fundus examination, Amsler test and by asking the subjects to answer the visual function questionnaires: EQ-5D, NEI-VFQ-25, as measures of health status quality and of the influence on welfare. The study revealed that under supplementation both control healthy subjects and patients with known degenerative retinal pathology included in the 50-60 years of age group evolved almost the same way, leading to the conclusion that administered xanthophyll pigments-based supplements, simple or enriched, managed to slow down the progression of abnormal degenerative vision loss to a rate comparable to physiological aging-related vision loss. It was also observed that intake of xanthophyll pigments dietary supplements preserved the general health condition and maintained relatively constant vision on the entire 36th months follow-up research duration in patients presented with existing age related degenerative retinal pathology at baseline. For healthy subjects, evaluation showed an improvement in results after dietary supplementation, with maintenance of constant vision and a significantly increase of general condition, in a positive sense. For subjects over the age of 60 dietary supplements intake was even more effective compared to younger group in providing better control of degenerative processes.